Regional structural change and the effects of job loss - Melanie Arntz; Boris Ivanov; Laura Pohlan (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
Routine-intensive occupations have been declining in many countries, but how does this affect individual workers' careers if this decline is particularly severe in their local labor market? This paper uses administrative data from Germany and a matched difference-in-differences approach to show that the individual costs of job loss strongly depend on the task-bias of regional structural change. Workers displaced from routine manual occupations have substantially higher and more persistent employment and wage losses in regions where such occupations decline the most. Regional and occupational mobility partly serve as an adjustment mechanism, but come at high cost as these switches also involve losses in firm wage premia. Non-displaced workers, by contrast, remain largely unaffected by structural change. – – In vielen Ländern sind routine-intensive Berufe rückläufig, aber wie wirkt sich dies auf die individuelle Karriere aus, wenn der Rückgang dieser Berufe im lokalen Arbeitsmarkt besonders stark ausfällt? Diese Studie zeigt basierend auf administrativen Daten aus Deutschland und einem mit Matching kombinierten Differenz-von-Differenzen-Ansatz, dass die individuellen Kosten eines Arbeitsplatzverlustes stark von der Tätigkeitsorientierung des regionalen Strukturwandels abhängen. Personen aus manuellen routine-intensiven Berufen haben nach einer Entlassung wesentlich höhere und lang anhaltende Beschäftigungs- und Lohnverluste in Regionen, in denen der Rückgang dieser Berufe am stärksten ausgeprägt ist. Regionale und berufliche Mobilität dienen teilweise als Anpassungsmechanismen, sie sind jedoch mit hohen Kosten verbunden, da diese Wechsel auch Verluste bei unternehmensspezifischen Lohnaufschlägen mit sich bringen. Beschäftigte, die nicht entlassen werden, bleiben hingegen weitgehend vom Strukturwandel verschont.
Keywords: J24; J63; J64; J65; O33; R11; 330; routine-biased structural change; local labor markets; displacement; mass-layoffs; plant closures; matching; difference-in-differences; event study